The Impact of Organizational Commitment on the E-services Quality in the Presence of the Organizational Learning as a Mediate Variable at Foreign Commercial Banks Operating in Jordan - Ahmad, Alaa Rawhy; Abu Hussain, Al-Hareth Mohmad (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to demonstrate the impact of organizational commitment in its dimensions (the continuous commitment, emotional commitment, and standard commitment) on the quality of electronic banking services represented by its dimensions (confidentiality, reliability, ease of use) by mediating organizational learning between the two variables in foreign commercial banks operating in Jordan. The researcher used the descriptive analytical method in data collection and analysis, and test hypotheses, where the study community is represented by foreign commercial banks operating in the governorate of Amman and the number of (Blom Bank, Bank Audi, Egyptian Arab land Bank, Citibank and Standard Chartered bank, National bank of Kuwait, and Rafidain Bank), while the sample of the study (225) employees of the researched banks was from (branch manager, department manager, assistant director, head of department), where electronic questionnaires were developed and distributed to the sample of the study, and all questionnaires were valid for study, and the data collected through the study questionnaire were analyzed using the Social Science SPSS and Smart PLS. The study concluded several results, most notably the existence of a statistically significant effect at the level of indication (0.05≥α) of the regulatory commitment to its dimensions (continuous, emotional, standard) on the quality of electronic services in their dimensions (confidentiality, reliability, ease of use) in foreign commercial banks operating In Jordan, the study found that after emotional commitment the strongest impact on the confidentiality and reliability of the banks researched as subdimensions of the quality of electronic banking services, as well as the analysis of the track showed a strong direct impact of regulatory commitment on both organizational learning and the quality of e-banking and at levels High. In light of the results of the study, the researcher presented several recommendations, the most important of which is the need for banks to improve their incentive levels in accordance with the personal needs of employees, and to improve the levels of support in all forms and types in order to preserve them, in addition to attention to the quality of electronic banking services provided to customers, and the need for the research banks to support their research and development departments in order to generate new knowledge, which may contribute to the creation of modern electronic banking services adapted to the Jordanian market, as the study recommended the need to follow the method of functional recycling to encourage the use of functional rotation methods to encourage Employees share knowledge among themselves and promote their teamwork culture.